2017
DOI: 10.1210/jc.2017-00881
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Classifier Based on Genome-Wide DNA Methylation Profiling in Well-Differentiated Thyroid Tumors

Abstract: Context:Even though the majority of well-differentiated thyroid carcinoma (WDTC) is indolent, a number of cases display an aggressive behavior. Cumulative evidence suggests that the deregulation of DNA methylation has the potential to point out molecular markers associated with worse prognosis.Objective:To identify a prognostic epigenetic signature in thyroid cancer.Design:Genome-wide DNA methylation assays (450k platform, Illumina) were performed in a cohort of 50 nonneoplastic thyroid tissues (NTs), 17 benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 37 publications
7
61
0
Order By: Relevance
“…ATC clustered separately from normal thyroid tissue both by expression and by methylation ( Figures 1 and 2), in line with previous studies [4,7,10,11] and showing that the tumor cell percentage was relatively high in the tumor samples. The expression signature of ATC was dominated by cell-cycle-related processes (Table S2), reflecting the high proliferative rate of this malignancy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…ATC clustered separately from normal thyroid tissue both by expression and by methylation ( Figures 1 and 2), in line with previous studies [4,7,10,11] and showing that the tumor cell percentage was relatively high in the tumor samples. The expression signature of ATC was dominated by cell-cycle-related processes (Table S2), reflecting the high proliferative rate of this malignancy.…”
Section: Discussionsupporting
confidence: 90%
“…The expression signature of ATC was dominated by cell-cycle-related processes (Table S2), reflecting the high proliferative rate of this malignancy. In regards to DNA methylation, the majority of differentially methylated CpGs in ATC were hypomethylated and in intergenic regions (Figure 2), in line with previous studies [10,11,24]. Global hypomethylation is a common phenomenon in cancer and is believed to be associated with genomic instability [25], agreeing well with the genomic complexity generally seen in ATC [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By using 450K arrays, Bisarro dos Reis confirmed that while DNA hypomethylation was predominant in PTC, hypermethylation was present in FTC and benign thyroid lesions. However, benign lesions showed significantly less numerous differentially methylated CpGs (222 hypomethylated and 1531 hypermethylated) with respect to FTC (1475 hypomethylated and 4100 hypermethylated) (Bisarro Dos Reis et al 2017). Importantly, the same study also suggested prognostic implications of the DNA methylation profile, with massive hypomethylation in aggressive (PDTC/ATC) thyroid cancer subtypes (Bisarro Dos Reis et al 2017).…”
Section: Introductionmentioning
confidence: 79%
“…However, benign lesions showed significantly less numerous differentially methylated CpGs (222 hypomethylated and 1531 hypermethylated) with respect to FTC (1475 hypomethylated and 4100 hypermethylated) (Bisarro Dos Reis et al 2017). Importantly, the same study also suggested prognostic implications of the DNA methylation profile, with massive hypomethylation in aggressive (PDTC/ATC) thyroid cancer subtypes (Bisarro Dos Reis et al 2017). Recently, Yim et al (2019) showed that a DNA methylation-based molecular method, named Diagnostic DNA Methylation Signature approach (DDMS), features high sensitivity/specificity in the identification of malignant and benign thyroid nodules.…”
Section: Introductionmentioning
confidence: 91%